2007
DOI: 10.1159/000110627
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Wisconsin Card Sorting Test Performance in Male Schizophrenic Patients: Influence of Dual Diagnosis

Abstract: Background: Different neuropsychological studies have shown schizophrenic patients to have executive function deficits, as illustrated by their performance in neuropsychological tasks such as the Wisconsin Card Sorting Test (WCST); certain studies have described a relationship between these deficits and negative symptoms. Schizophrenic patients also exhibit a high lifetime prevalence (40–50%) of comorbid substance use disorders (SUDs). However, little attention has been paid to this comorbidity (dual diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 118 publications
0
11
1
Order By: Relevance
“…This is an important new finding. Comparing the three main previous studies 9 10 23 with the current study, we summarised shared and different findings, shown in table 4.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is an important new finding. Comparing the three main previous studies 9 10 23 with the current study, we summarised shared and different findings, shown in table 4.…”
Section: Discussionmentioning
confidence: 79%
“…In a different study, age affected PE score but education years did not affect either CA or PE scores 10. Additional two studies showed age of onset affected PE score23 and the positive and negative syndrome scale (PANSS) negative scale score affected CA score in patients with schizophrenia 9. These findings indicate that it is important to consider all clinical and sociodemographic factors to clarify which affect WCST scores in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Inconsistency of findings could also be due to differing sociodemographic or clinical characteristics of the samples, such as age, intelligence or general cognitive functioning [60], treatment, clinical state at the time of the study, or comorbidity with other disorders. In this respect, our group has recently reported that the association between negative symptoms and executive function is found in schizophrenic patients without substance use disorder history, but not in patients with this history [63,64]. …”
Section: Introductionmentioning
confidence: 99%
“…Of the 18 studies involving schizophrenia and abuse of mixed psychoactive substances, almost half (n = 8) did not find differences in cognitive functioning between patients with schizophrenia and comorbid substance use disorders compared to those without comorbid substance use disorders (Addington & Addington, 1997;Barnes, Mutsatsa, Hutton, Watt, & Joyce, 2006;Cleghorn et al, 1991;Harrison et al, 2008;Krysta, Krupka-Matsuszczyk, & Klaslik, 2005;Pencer & Addington, 2003;Rodriguez-Jimenez et al, 2008;Thoma & Daum, 2008). On another note, six studies showed that mixed psychoactive substance abuse was associated with better cognitive functioning in schizophrenia (Herman et al, 2004;Joyal et al, 2003;McCleery et al, 2006;Potvin et al, 2005;Sevy et al, 2001;Thoma et al, 2007), especially for speed of processing (four studies) and language/verbal abilities (fluency; four studies).…”
Section: Studies Of Mixed Psychoactive Substancesmentioning
confidence: 99%